Inspiring a Revolution: A review of Julio Cammarota and Michelle Fine’s Revolutionizing Education: Youth Participatory Action Research in Motion - Alison E. Leonard (Networks: An Online Journal for Teacher Research, 2010)
Multigenerational, diverse voices can be heard throughout Julio Cammarota and Michelle Fine’s Revolutionizing Education: Youth Participatory Action Research in Motion, an edited collection of chapters presenting provocative, transformative participatory action research (PAR)—focusing on youth participatory action research (YPAR). Challenging conventional notions of inquiry, these YPAR projects illustrate “research conducted “with” as opposed to “on” youth,” (p. vii) surrounding issues of injustice, inequality, and struggles in the lives and education of youth and their communities, giving voice to those often silenced due to age, race, ethnicity, sexuality, economic status, gender, language, and abled/disabled identities. Although of interest and targeting action researchers and scholarly audiences in education, Revolutionizing Education also speaks to administrators, youth researchers, documentarians, and teachers, particularly since the work involves co-constructed projects involving adults and youth. It, thus, lends itself to broadening the possibilities of teacher research.